Peripheral Neuropathy Burden in Hemodialysis and Liver Cirrhosis in a Sample of Egyptian Patients - Mohammad Hassan (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Chronic kidney disease [CKD] and liver cirrhosis [LC] are significant public health challenges in both developed and developing countries, resulting in an impairment in quality of life worldwide. Patients' morbidity and mortality are primarily due to neurological problems that occur as a result of these conditions. Peripheral neuropathy [PN] is a common neurological complication that has been related to the severity of the disability.    The aim of the work: To evaluate the prevalence and patterns of PN in cirrhotic and uremic patients on hemodialysis [HD] at Al-Azhar University Hospitals in Cairo, Egypt. Patients and Methods: A cross-sectional study was performed on patients recruited from nephrology unit, tropical and internal medicine departments at Al-Azhar University Hospitals in Cairo. Sixty HD patients and sixty cirrhotic patients were investigated. All patients were submitted to clinical evaluation as well as electrophysiological studies and laboratory investigations. Results: Neuropathy was diagnosed in 76.7% and 73.3% of HD and LC groups respectively. Patients with neuropathy showed significantly higher duration of dialysis and cirrhosis in both groups, higher urea and potassium levels and autonomic presentation [39.1%] in HD group and higher grades “B” & “C” in Child-Pugh classification and motor [18.2%] and asymptomatic [29.5%] presentations in LC group. Sensory symptoms were present in 45.7% and 34.1% in HD and LC groups respectively with no significant difference. Both axonal and mixed types were insignificantly more prevalent than pure demyelinating neuropathy in both groups. Conclusion: The present study emphasized the high prevalence of PN in patients with CKD on HD and patients with LC with different patterns of presentation denoting wide variety of pathological mechanisms.